2013
DOI: 10.4100/jhse.2012.8.proc2.21
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the perception of physical activity, eating habits, self-efficacy and the knowledge about healthy food in Albanian adolescents

Abstract: ABSTRACTÇitozi R, Bozo D, Pano G. An assessment of the perception of physical activity, eating habits, self-efficacy and the knowledge about healthy food in Albanian adolescents. J. Hum. Sport Exerc. Vol.8, No. Proc2, pp. S192-S203, 2013. Objective: The present study evaluates eating habits and behaviors, and nutritional and food safety knowledge of a group of Albanian adolescents. Design: A dietary questionnaire previously constructed and tested was self-administered during school time. Each section was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 36 publications
0
9
2
Order By: Relevance
“…(5) In contrast Çitozi et al (2013) reported that only 2.6% of the Albanian female school students were obese and 14.7% were overweight, and 3.8% of females were underweight. (9) In the present study, there was significant increase in total scores of attitude and behavior of healthy dietary habits after the intervention, but not in total knowledge score. Also, this intervention has led to significant decrease in the mean scores of barriers.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…(5) In contrast Çitozi et al (2013) reported that only 2.6% of the Albanian female school students were obese and 14.7% were overweight, and 3.8% of females were underweight. (9) In the present study, there was significant increase in total scores of attitude and behavior of healthy dietary habits after the intervention, but not in total knowledge score. Also, this intervention has led to significant decrease in the mean scores of barriers.…”
Section: Discussioncontrasting
confidence: 65%
“…(8) Factors H Original Article inducing eating behaviors have to be better understood in order to develop effective nutrition interventions. (9) Barriers to healthy eating in adolescents include a lack of time, limited availability of healthy foods lack of concern about for eating healthy food. (10) Chen et al (2015) recommended that interventions are needed to assist adolescents in adopting healthy eating behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Diet and nutrition play important roles in maintaining health and preventing numerous diseases [4]. A decrease in morbidity and mortality associated with lifestyle health diseases may be achievable if healthy EHs are adopted early in life and maintained in the long term [8].…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining a healthy body weight is important for overall health and can help prevent and control many diseases and conditions [4]. Previous studies in Saudi Arabia and Arab countries have concluded that Arab women face more perceived barriers to healthy lifestyle than men, particularly for PA [39,[51][52][53][54].…”
Section: Eating Habits and Perceived Barriers To Healthy Eatingmentioning
confidence: 99%
See 1 more Smart Citation